Structural load monitoring of floating mooring column and its application on optimal regulation for water conveyance system operation of sea shiplock - Qi, Junlin; Li, Lexin; Jiang, Tao; Xiang, Zhouyu; Yang, Jia; Wu, Linjian (Frontiers in Energy Research, 2023)
Due to the sea water intrusion and the development trend of using large-scale ships, more stringent requirements are put forward for the safety of water delivery process and the mooring equipment operation for the sea shiplock. The maximum loads for the mooring equipment of sea shiplock, i.e., floating mooring column (FMC), are generally occurred at the end of water delivery. The superimposed effect of turbulent flow and marine corrosive environment can accelerate the failure of the floating mooring column structure for the sea shiplock, which leads to the safety incidents, including the structural damage of FMC and the breakage of mooring lines for the ship, etc. The safety of the FMC is mostly influenced by three factors, including the ship's tonnage, the water flow environment of the locked room, and the lock operation technologies; among these, the water flow environment can be considered the most significant. In practice, because the mooring load of an FMC due to water delivery from the shiplock is very complicated, there is currently no mature approach to condition monitoring. This investigation aims to address a large sea shiplock, and the optimal regulation approach for water delivery of shiplock is established based on a load monitoring methodology for FMCs. The detection accuracy of the FMC mooring loads is controlled by simulation verification with errors less than 10%. During the optimized water delivery process, the exerted loads on the FMCs are noticeably reduced to be lower than the maximum design rating. The innovative approach is essentially based on an inversion calculation of the load response model for obtaining the mooring loads of FMCs, with the monitored load results used to regulate and optimize the water delivery process of the shiplocks. The research results can fill a part of the research gap of FMC mooring load condition monitoring method in shiplock water delivery, and provide technical support for the safety of shiplock water delivery process and mooring equipment operation.